DEWAN PENDIDIKAN DI TENGAH PUSARAN COVID-19 - kholilur Rahman (Universitas Yudharta Pasuruan, 2019)
It is probably almost a consensus of experts that the Covid-19 pandemic is an undiscovered virus, and its negative impact touches almost the entire joints of human life; Social, economic, banking, tourism, and education. The impact of the life joints mentioned at the beginning may be overcome by certain stimuli and within a certain period of time can be recovered. But the impact that touches the joints of the last Life (education), especially related to the quality of education, the Resolution requires "collective ijtihad" with a wide range of perspective, and must be sustained by the comprehensive stimulus. Given the whole quality of the joints of human life is determined by the quality of education. In order to collective ijtihad against the impact of the Covid-19 in this field of education, there is an honorable institution that loses its "fangs". The Board of Education (especially the District Education Council) as a representation of the community in the field of education should present contribute its role to help the heavy burden of society in education, especially in the midst of the Covid-19 vortex and its impacts, The Board of Education must be able to attend: (a) as a advisory agency for local governments in the determination of the implementation of education policies, especially during the pandemic Covid-19 period; (b) As supporting agency, whether financial, thinking or energy for exclusivity in the organizing of education; (c) As a controlling agency for the education policy of the local government; and (d) as a mediator agency on policies implemented by exclusivity and legislative